Transport Direction and Scandinavian Source Regions of the Saalian Glacial and Glaciofluvial Deposits in a Case Study of Łubienica-Superunki (Central Poland) - Maria Górska-Zabielska; Ewa Smolska; Lucyna Wachecka-Kotkowska (Minerals, 2021)
The article contains detailed petrographic studies, which covered a coarse and medium-grain gravel fraction of two layers of glacial till (units ŁS II and ŁS IV) and two layers of sand-gravelly outwash deposits (units ŁS I and ŁS III) related to the Odranian Glaciation (MIS6, Saalian) in Łubienica-Superunki, North Mazovian Lowland, central Poland. Additionally, the indicator erratics were identified to indicate their Scandinavian source areas and the directions of the ice sheet transgressions. This case study is discussed against the background of similar sediments and forms from the same age but from other places in the Polish Lowlands. Regardless of the facies types and fractions, crystalline rocks dominated over all other petrographic groups in all samples. The most common were the indicator erratics derived from the Åland Islands, followed by those from the south-eastern area of Sweden (Småland) and from Dalarna in central Sweden. Amongst the erratics of limited indicative significance, the most common were Lower Palaeozoic limestones and the Jotnian red sandstones. The complex petrographic analyses point to the dipartite nature of the studied profile. This separateness was confirmed by the TBC: 59.1–59.2° N and 18.0–18.2° E for the lower units and 58.8–59.4° N and 17.3–17.9° E for the upper ones.